Lilli-Pilli's sister - Branford, Anna; Catchlove, Linda (Newtown, NSW : Walker Books Australia Pty Ltd, 2014)
Lilli-Pilli's mother is having a baby. Lilli-Pilli is sure the baby is going to be a sister. She can feel it in her wings.
"For primary school age" -- Copyright screen.
Title from title screen.
Also available in print.
Mode of access : Available online.
Keywords: Fairies -- Juvenile fiction; Fairies; Children's stories; Fiction